Pacar Berhubungan dengan Perilaku Seks Pranikah pada Remaja - Siti Qomariah (Jurnal Kesmas Asclepius, 2020)
This study aimed to determine the relationship of boyfriends to sexual behavior in adolescents in SMP Negeri 16 Sukajadi subdistrict Pekanbaru. The research method used is analytic quantitative observational (cross-sectional). The results of the univariate analysis of the majority of respondents aged 12 years amounted. The majority of the sexes are women and are Muslim; the majority behave negatively. Bivariate analysis results obtained p-value (0,000) <a = 0.05. In conclusion, there is a relationship of boyfriends to premarital sexual behavior among teenagers in SMP Negeri 16 Kec. Sukajadi Pekanbaru. Keywords: Behavior, Teenagers, Premarital Sex